A novel siRNA–gemcitabine construct as a potential therapeutic for treatment of pancreatic cancer. (11th August 2020) - Simonenko, Vera; Lu, Xiaoyong; Roesch, Eric; Mutisya, Daniel; Shao, Chunbo; Sun, Qian; Patterson-Orazem, Athéna; McNair, Marcus; Shanmuganathan, Aranganathan; Lu, Patrick; Evans, David M
Abstract: The non-nucleoside analog gemcitabine has been the standard of care for treating pancreatic cancer. The drug shows good potency in pancreatic cancer cells in vitro but, due to poor bioavailability, requires administration in large doses by infusion and this systemic exposure results in significant toxicity for the patient. Genes have been identified that, when silenced by siRNA, synergize with gemcitabine treatment and offer a means of reducing the gemcitabine dosage required for efficacy. However, benefiting from the synergism between the two agents requires that the gemcitabine and siRNA penetrate the same cells. To ensure co-delivery, we incorporated gemcitabine covalently within siRNAs against targets synergistic with gemcitabine (CHK1 or RAD17). We demonstrated that specific bases within an siRNA can be replaced with gemcitabine to increase efficacy. The result is a single drug molecule that simultaneously co-delivers gemcitabine and a synergistic siRNA. The siRNA–gemcitabine constructs demonstrate a 5–30-fold improvement in potency compared with gemcitabine alone. Co-delivering a CHK1 siRNA–gemcitabine construct together with a WEE1 siRNA resulted in a 10-fold improvement in IC50 compared with gemcitabine alone. These constructs demonstrate efficacy across a wide array of pancreatic tumor cells and may represent a novel therapeutic approach for treating pancreatic cancer.